2013
DOI: 10.1095/biolreprod.112.104653
|View full text |Cite
|
Sign up to set email alerts
|

Semen Parameters Can Be Predicted from Environmental Factors and Lifestyle Using Artificial Intelligence Methods1

Abstract: Fertility rates have dramatically decreased in the last two decades, especially in men. It has been described that environmental factors as well as life habits may affect semen quality. In this paper we use artificial intelligence techniques in order to predict semen characteristics resulting from environmental factors, life habits, and health status, with these techniques constituting a possible decision support system that can help in the study of male fertility potential. A total of 123 young, healthy volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 72 publications
0
46
0
2
Order By: Relevance
“…In the present study, we construct two artificial neural networks, one to predict the overall seminal profile, and a second for the prediction of characteristics of sperm concentration. Similar studies were conducted only by Girela et al (2013), Gil et al (2012) and Sahoo and Kumar (2014). In their study, Sahoo and Kumar (2014) created the MLP model to predict the general semen profile.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In the present study, we construct two artificial neural networks, one to predict the overall seminal profile, and a second for the prediction of characteristics of sperm concentration. Similar studies were conducted only by Girela et al (2013), Gil et al (2012) and Sahoo and Kumar (2014). In their study, Sahoo and Kumar (2014) created the MLP model to predict the general semen profile.…”
Section: Discussionmentioning
confidence: 90%
“…The values in the current article are 85.12%, 84.93% and 0.812, respectively (Table 9). Girela et al (2013), based on survey responses developed two MLP models to predict the motility and sperm concentration. On the basis of the factors used to evaluate the effectiveness of the test, it can be concluded that we were able to create more effective predictive models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many lifestyle choices, such as tobacco smoking, have long been considered as impairments of male fertility (Girela et al 2013). Epidemiological and clinical studies have discovered significant declines in sperm density, sperm mobility, semen volume (Kü nzle et al 2003, Ramlau-Hansen et al 2007) and the percentage of normal sperm morphology in smoking populations (Trummer et al 2002, Gaur et al 2007.…”
Section: Introductionmentioning
confidence: 99%